2004
DOI: 10.1148/radiol.2302020761
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass: Manual and Automatic Segmentation of True FISP and FLASH Cine MR Images in Dogs and Pigs

Abstract: LV mass was determined most accurately by using manual contours on true FISP images. In these animal models, fully automatic segmentation of true FISP images was performed in one-sixth of the time of manual segmentation and yielded LV masses with a mean error of approximately 5% of true LV mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 28 publications
1
62
0
Order By: Relevance
“…However, some deterioration of the variability in the apical region was evident. There was also slightly higher (albeit not statistically significant) interobserver variability in the apical region, which reflects the general difficulty of determining the correct alignment parameters in this region due to suboptimal image quality (10).…”
Section: Discussionmentioning
confidence: 86%
“…However, some deterioration of the variability in the apical region was evident. There was also slightly higher (albeit not statistically significant) interobserver variability in the apical region, which reflects the general difficulty of determining the correct alignment parameters in this region due to suboptimal image quality (10).…”
Section: Discussionmentioning
confidence: 86%
“…These studies included only healthy volunteers and did not assess the morphological changes of the displaced structures within the cardiac cycle. The cine trueFISP sequence is a fast and robust technique allowing a real-time visualisation of the heart's ventricular wall movement [18,19]. A recent study [26] reported a lack of brain ventricular volume changes during a Valsalva procedure in patients with communicating hydrocephalus using a cine trueFISP sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast is determined by the ratio of T2 to T1 rather than the inflow effects [18]. Relative to spoiled gradient-echo methods, the trueFISP sequence has an excellent temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] The MRI technique provides ventricular measurements within 5% of the true gross anatomic measurements at autopsy. 24,26 We have adapted this technique during VF.…”
Section: Discussionmentioning
confidence: 99%